Demographic Characteristics of COVID-19 Patients in District Gujrat - Hussnain Ashraf Gondal ,Hassan Mumtaz ,Irfan Afzal Mughal ,Noor-ul-Ain Irfan ,Shameem Mumtaz (Journal of Rawalpindi Medical College, 2020)
Objective: To determine the prevalence of Covid-19 in the district of Gujrat, its association with gender, age, its correlation with respiratory and cardiac symptoms and to find the link of this disease with travel history of patients to affected areas. Methodology: A total of 222 COVID-19 -Positive patients (Male and Female) out of 514 clinically suspected cases (fever, cough, dyspnoea, lethargy & anosmia) as per WHO guidelines were selected. The use of the data for research purposes was explained to patients, and informed consent was taken. The study was approved by the ethical committee of Aziz Bhatti Shaheed Hospital. Samples were extracted from nasopharyngeal swabs using standard extraction protocol. Statistical tools used was SPSS Version 24. Chi-square test and correlation of age with respiratory and cardiac symptoms was calculated. Results: Male gender was significantly affected by this disease (P=0.001) as compared to the female gender. Regarding the prevalence of respiratory symptoms, 31(14%) were asymptomatic. 37(16.7%) had Dyspnea, 45 (65.3%) cough (P= 0.001). Nine (4.1%) developed pneumonia. Fever and Cough was the most common symptom in the age group 21-40 yrs(P=0.001). While pneumonia developed in the older age group. The cardiac symptoms appeared in young age group (p=0.000) in the age group 21-40 yrs (70.9% n=78).38 patients (17.2%) had the symptom of chest pain, 24(10.9%) tachycardia and 1(0.5%) developed arrhythmia. Out of 222 COVID positive patients, 67.1% (149) gave a history of direct contact with positive patients, 19.8% (n=44) gave travel history,4.5% (n=10) had a history of going to Raiwind Ijtamah and 8.6% (n=19) were zaireen/pilgrims from Taftan. Conclusion: The COVID -19 is comparatively more common in male patients. 50% of the patients were of age group 21-40 years showing the symptoms of fever and cough along with mild cardiac symptoms. Acute pneumonia developed in older age groups while cardiac symptoms were significant in young age. In Gujrat District, the majority of the patients (67.1%) developed Covid-19 due to travelling.